Pengaruh Standar Operasional Prosedur (Sop) Dan Lingkungan Kerja Terhadap Produktivitas Kerja Karyawan Pada PT. Agro Perak Sejahtera Bengkulu Utara - Setiawati, Juni; Arianto, Tezar (Jurnal Fokus Manajemen, 2024)
With work productivity, it is expected that work can be carried out effectively and efficiently, so this is very necessary in achieving the goals that have been set. Many things affect work productivity, including SOPs and work environment. This research belongs to the category of quantitative research, which aims to explain the relationship between the independent variable and the dependent variable. The research method used is a quantitative approach, focuses on objective phenomena, and is applied to investigate populations as well as specific samples in research. The sampling in this study was a total sampling of 55 employees of PT. Agro Perak Sajahtera North Bengkulu. From the table above, it can be seen that the significance value of F is 0.000 < 0.050 and Fcalculate > Ftable, 104,038 > 3,17 from the results of data management, it can be concluded that all independent variables, namely variables (Standard Operating Procedures and Work Environment) simultaneously or together have a significant effect on the dependent variable, namely Employee Work Productivity (Y). This means Ho is rejected and Ha is accepted. Based on and discussion of partial test results of research on the Effect of Standard Operating Procedures and Work Environment on Employee Work Productivity at PT. Agro Perak Sajahtera North Bengkulu, it can be concluded that: Standard Operating Procedures have a positive effect on the Work Productivity of PT. Agro Perak Sajahtera North Bengkulu. Work Environment has a positive effect on the Work Productivity of PT. Agro Perak Sajahtera North Bengkulu.